Meiotic behavior and H3K4m distribution in B chromosomes of Characidium gomesi (Characiformes, Crenuchidae) - Serrano, érica Alves [UNESP] (2016)
Characidium gomesi Travasso, 1956 specimens from the Pardo River have up to four heterochromatic supernumerary chromosomes, derived from the sex chromosomes. To access the meiotic behavior and distribution of an active chromatin marker, males and females of C. gomesi with two or three B chromosomes were analyzed. Mitotic chromosomes were characterized using C-banding and FISH with B chromosome probes. Meiocytes were subjected to immunofluorescence-FISH assay using anti-SYCP3, anti-H3K4m, and B chromosomes probes. Molecular homology of supernumeraries was confirmed by FISH and by its bivalent conformation in individuals with two of these chromosomes. In individuals with three Bs, these elements formed a bivalent and a univalent. Supernumerary and sex chromosomes exhibited H3K4m signals during pachytene contrasting with their heterochromatic and asynaptic nature, which suggest a more structural role than functional of this histone modification. The implications of this result are discussed in light of the homology, meiotic nuclear organization, and meiotic silencing of unsynapsed chomatin.